Analisis Produksi Pertanian Kakao Di Kecamatan Nangapanda Kabupaten Ende - Damianus Tola (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
This study aims to indentify input factors influence toward cocoa agricultural productivity and cocoa farmer income at Nagapanda district in Ende Regency. This research hoped useful for the Ende Regency to evaluate policies so capable to increasing cocoa agriculture. This study uses primary data which is obtained bydistrbuting a quetioner to 100 samples in order to define the input defference of the field area, worker seed, tools, chemical, and fertilizer used to obtain cocoa agricultural productivity increment. Sample taking method use simple non probability sampling that is proposive sampling. Proposive sampling is taking sample from population based on certain criteria. The used criteria can be based on certain judgement. The used analysis tool is double analyses regretion, statical test, econometric test, and measuring the cocoa farmer production differences. Statistic test showed that field area factors, workers, tools, chemical, and fertilizer give significant influence to cocoa agricultural productivity at Nangapanda distric while seed factors give less signifcant influence (?=0,415); there are cocoa agriculture prpoductivity diference between zozozea villagen and rapowawo village where zozozea village is more productive ( t = 2,557, p = 0,006). Statiscaly, there is a siginificant diffrence cocoa farmers level in zozozea 98,405 kg and Rapowawo village 69.021 kg.